2019
DOI: 10.1093/neuonc/noz079
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic HSV therapy increases trametinib access to brain tumors and sensitizes them in vivo

Abstract: Background Hyperactivation of the RAS-RAF-MEK-ERK signaling pathway is exploited by glioma cells to promote their growth and evade apoptosis. MEK activation in tumor cells can increase replication of ICP34.5-deleted herpes simplex virus type 1 (HSV-1), but paradoxically its activation in tumor-associated macrophages promotes a pro-inflammatory signaling that can inhibit virus replication and propagation. Here we investigated the effect of blocking MEK signaling in conjunction with oncolytic H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…These findings are in line with prior studies of multiple tumors types treated with OV that demonstrate a modulated immune response to OV administration that contributes to control of tumor growth [47][48][49][50] . However, because this immune response is also responsible for the rapid clearance of viral particles, a delay in OV elimination could improve the therapeutic efficacy of this anti-cancer treatment strategy [51][52][53][54][55] .…”
Section: Discussionsupporting
confidence: 90%
“…These findings are in line with prior studies of multiple tumors types treated with OV that demonstrate a modulated immune response to OV administration that contributes to control of tumor growth [47][48][49][50] . However, because this immune response is also responsible for the rapid clearance of viral particles, a delay in OV elimination could improve the therapeutic efficacy of this anti-cancer treatment strategy [51][52][53][54][55] .…”
Section: Discussionsupporting
confidence: 90%
“…We have shown that RAMBO virus, an oHSV expressing an anti-angiogenic gene Vasculostatin, reduces endothelial cell migration and angiogenesis, thereby aiding in the reduction of tumor growth. In addition, we have shown that RAMBO virus also reduces an oHSV therapy-induced innate inflammatory response in part through the suppression of TNFα secretion from macrophage/microglia [31,32]. This allows for an enhancement in virus replication and longer viral presence in in vivo than control viruses (rHSVQ).…”
Section: Discussionmentioning
confidence: 98%
“…In addition to the direct killing of tumor and tumor endothelial cells, OV therapy activates innate and adaptive antitumor immunity, thereby inflaming the cold tumor into hot TME. Although oHSV replication and propagation can be limited by the antiviral innate immune response, the initial local tumor cell killing by virus infection can reverse the immunosuppressive TME, thereby resulting in tumor associated antigen (TAA) release, cross-presentation, and antitumoral T cell recruitment [31,32]. Therefore, fine-tuning of oHSV-triggered early innate immune responses by effectively increasing the virus propagation and antitumor immune response is important to maximize the therapeutic efficacy of oHSV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, some tumors may be, or may become, resistant to oHSV due to the pro-inflammatory response of tumor-associated macrophages (via a constitutively activated MEK or STAT signaling) in the tumor milieu, which blunts oHSV replication. The pharmacological blockade of these intracellular pathways in tumor-associated macrophages, and the overall modulation of the host inflammatory response to the virus, can restore oHSV replication in tumor cells and the consequent oHSV-related CD8+ T cell activation, responsible for the antitumor effect observed in animal models [155][156][157]. In turn, the alteration of the tumor microenvironment, following oHSV replication, can enhance the chemotherapeutic drug's diffusion to (and efficacy against) the tumor.…”
Section: Ohsv Combination Therapies and Immunotherapiesmentioning
confidence: 99%